Iceland : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Iceland discusses that after years of robust growth, economic activity has significantly weakened. Supply disruptions in tourism, the engine of recent growth, and the associated uncertainty have triggered a drop in domestic demand and an increase in unemployment. A swift policy response, with fiscal relaxation and monetary easing, has stabilized expectations and cushioned the effects. A moderate but fragile growth recovery is expected in 2020. Macroprudential measures are helping to preserve buffers for managing financial stability risks. Macroprudential policies are adequate, given still elevated household debt and real-estate prices and benign external financing conditions. Looking forward, the macroprudential toolkit could be expanded to contain potential risks in the loan portfolio over the medium term. Ongoing education reforms would boost human capital and productivity, greater transparency of large unlisted companies would preserve the business environment, and strategic policies in tourism and fisheries would protect the sustainability of traditional economic sectors.